The Adverse Impact of Glaucoma on Psychological Function and Daily Physical Activity - Wenbin Huang; Kai Gao; Yaoming Liu; Mengyin Liang; Xiulan Zhang (Journal of Ophthalmology)
Purpose. To evaluate the impact of glaucoma on vision-related quality of life and physical activity. Methods. This study included 50 glaucoma patients and 50 healthy control subjects. Sociodemographic and clinical data were collected from all subjects. A Chinese version of the NEI VFQ-25 was used to evaluate the quality of life. Objective physical activity was assessed by wearing an accelerometer for 7 consecutive days. Results. No significant difference was found in sociodemographic data between the two groups (all p<0.05). Visual acuity and visual field scores were worse in the glaucoma group than in the control group (all p<0.001). The VFQ-25 scores indicated significantly lower scores for ocular pain, social function, mental health, role difficulties, and color vision in the glaucoma group than in the normal group (all p<0.05). The average daily step count was lower in the glaucoma group than in the normal group. High, moderate, and low average daily step counts in the glaucoma group were associated with early-, moderate-, and advanced-stage glaucoma, respectively, while the step count was significantly lower in the advanced-stage glaucoma group than in the control group p=0.037. A positive relationship was found between the average daily step count and social function and mental health (both p<0.05). Conclusions. We demonstrated an adverse impact of glaucoma on psychological function and daily physical activity. Social function and mental health showed declines in glaucoma patients, and physical activity was limited in patients with advanced-stage glaucoma.